Weight status and psychosomatic complaints in Swedish adolescent boys and girls: does family support play a buffering role? - Jasmin Venäläinen; Sara Brolin Låftman; Jonas Landberg (BMC, 2024)
Abstract Background Psychosomatic complaints have increased among adolescents in recent decades, as have overweight and obesity rates. Both of these trends are regarded as public health concerns. However, the associations between weight status and psychosomatic complaints are not yet clear, necessitating further research. The aim of the present study was to investigate the associations between weight status and psychosomatic complaints in Swedish adolescent boys and girls, as well as to explore the potential buffering effect of family support. Methods The data was obtained from the cross-sectional Swedish Health Behaviour in School-aged Children (HBSC) study conducted in 2017/18, which involved 3,135 students aged 11, 13, and 15 years. Weight status was based on self-reported information on weight and height, which allowed for the calculation of body mass index (BMI) and the categorisation of participants into three groups: non-overweight, overweight, and obese. Psychosomatic complaints were assessed based on information regarding the frequency of eight different complaints, which were summed into an index. Family support was measured using three items describing the level of perceived emotional support, and an index was created, which was dichotomised into low and high family support. Gender stratified linear regression models were run to examine the associations between weight status and psychosomatic complaints. Age and family affluence were included as covariates. Interaction terms were included to evaluate whether family support moderated the main association. Results Obesity was associated with higher levels of psychosomatic complaints in both boys and girls when compared to being non-overweight (boys: b = 2.56, 95% CI 0.32, 4.79; girls: b = 3.35, 95% CI 0.77, 5.94), while being overweight did not show any statistically significant associations with the outcome (boys: b = 0.21, 95% CI -0.72, 1.15; girls: b = 0.78, 95% CI -0.42, 1.98). In girls, a statistically significant interaction effect between family support and weight status was observed (p = 0.031), indicating that family support buffered against psychosomatic complaints in girls with obesity. No statistically significant interaction was found for boys (p = 0.642). Conclusions The findings of this study highlight the importance of public health initiatives aimed at preventing childhood obesity. They also underscore the significant role of family support in reducing psychosomatic complaints among adolescents with obesity. Further research is necessary to gain a deeper understanding of these relationships.